Analisis “overthinking sebagai refleksi pribadi” dalam karya penciptaan seni lukis sarfi - Lalu Aswandi Mahroni G (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This research and art creation aim to explore the psychological condition of "overthinking" as a source of ideas and personal reflection in creating paintings. Overthinking is often considered a mental burden and a trigger for anxiety, but in this context, it is transformed into creative energy visualized through a symbolic expressionism approach. The creation method used includes the stages of observation, contemplative self-reflection, sketch designing, and the realization of the artwork using mixed media techniques on canvas. The materials used vary, including acrylic paint, gypsum, spray paint (pilox), printed paper, and markers, to create emotional textures and dimensions. The result of this process is a series of expressionist paintings which visually represent inner conflicts, social pressures, and future uncertainties. Through these works, the author finds a cathartic medium to manage emotions while inviting appreciators to understand dark psychological experiences. In conclusion, this art creation proves that overthinking can be reconstructed into critical awareness and a powerful visual communication medium.